Alumina-plated biaxially oriented polylactic acid film with high barrier property and preparation method of alumina-plated biaxially oriented polylactic acid film
By adding high crystalline materials to the polylactic acid film and forming an alumina layer, the problem of insufficient oxygen and water vapor resistance of polylactic acid film is solved, and the combination of high barrier properties and transparency is achieved, which expands its application in the food packaging field.
Patent Information
- Application Number
- CN202411738652.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-11
AI Technical Summary
The existing polylactic acid films have poor oxygen and water vapor resistance, and the aluminum plating process causes the film to lose its transparency, limiting its application in the food packaging field.
A high-barrier aluminum oxide bidirectional stretch polylactic acid film is used to plating high-corrosive materials such as P3HB, P3HV, PGA, PEF or PECF to the polylactic acid film, and an alumina layer is formed in vacuum evaporation treatment to improve the heat resistance and transparency of the film.
It achieves the improvement of high barrier performance, while maintaining the transparency of the film, expanding its application in the food packaging field, and improving the heat resistance and mechanical strength of the film.
Smart Images

Figure CN119590067A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material films, and in particular to a high-barrier aluminum oxide-plated biaxially stretched polylactic acid film and a preparation method thereof. Background Art
[0002] Existing polymer plastic films are usually made of non-degradable materials such as polypropylene and polyethylene. The use of these non-degradable films will cause environmental pollution. Polylactic acid (PLA) is a biodegradable plastic that can be decomposed by microorganisms, enzymes, etc. in the natural environment without causing pollution to the environment. At the same time, PLA has good mechanical properties. However, PLA has poor oxygen and water vapor barrier properties and cannot meet the barrier performance requirements of packaging products. Patent CN116278287 discloses an aluminum-plated BOPLA film, which is divided into a surface layer, a core layer and an inner layer. The weight ratios of crystalline PLA and non-crystalline PLA in each layer are: the inner layer is (23.5~30.0): (69.4~74.5), the core layer is (92.5~94.5): (5.5~7.5), the surface layer is all crystalline PLA, and the aluminum-plated layer is combined with the inner layer. The water vapor permeability of the patented film can be as low as 3.00 g / (m 2 ﹒ 24h), oxygen transmission rate can be as low as 5.00 ml / 24h﹒ m 2 ﹒ 0.1MPa).
[0003] Although this method solves the problem of insufficient barrier properties of PLA film, PLA has poor heat resistance due to its poor crystallinity. The high temperature radiation of 1000°C from the heating boat will cause the BOPLA film with poor heat resistance to bend and deform during the aluminum plating process, ultimately resulting in insufficient aluminum plating flatness and large differences in aluminum plating fastness. In severe cases, the aluminum oxide film layer and the plastic layer will be delaminated and even detached. At the same time, the aluminum plating process causes the BOPLA film to lose its transparency, limiting the application of high-barrier PLA film in the field of food packaging. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the above-mentioned technologies, the present invention provides a high barrier aluminum oxide-coated biaxially stretched polylactic acid film and a preparation method thereof. Aluminum oxide coating can also improve the oxygen barrier and water vapor barrier properties of the biaxially stretched polylactic acid film, and can also solve the problem of poor transparency of aluminum-coated BOPLA. The aluminum oxide-coated biaxially stretched polylactic acid film has high barrier properties and can also maintain good transparency. Poly 3-hydroxybutyrate (P3HB) and poly 3-hydroxyvalerate (P3HV) in polyhydroxyalkanoates (PHA), polyglycolic acid (PGA), polyethylene 2,5-furandicarboxylate (PEF) or furan copolyester PECF are also degradable plastics. At the same time, these polymers have high crystallinity and crystallinity, providing the material with good heat resistance and mechanical strength. The heat resistance of PLA can be enhanced by adding corresponding PHA and PGA, PEF or PECF, and the rigidity and stiffness of PLA can also be enhanced. The improvement of heat resistance reduces the thermal shrinkage of BOPLA film during aluminum plating, which is beneficial to the aluminum plating fastness, and the high rigidity of the film is also beneficial to its stability during vacuum evaporation treatment. However, the modification of PLA by conventional rigid particles will reduce the elongation at break of the film while increasing its rigidity, making the film brittle, which is not conducive to the biaxial stretching process of the film. In order to prevent the PLA film from becoming brittle, a sufficient amount of compatibilizer can be added to make the film not brittle while increasing its rigidity. To achieve this object, the present invention adopts the following technical solutions: A high-barrier aluminum oxide-coated biaxially stretched polylactic acid film, comprising a plastic base layer and an aluminum oxide layer, wherein the film base layer is a three-layer co-extruded biaxially stretched film consisting of a surface layer, a core layer and an inner layer in sequence; the inner layer is combined with the aluminum oxide layer; The surface layer and the inner layer include the following raw material components by mass fraction: polylactic acid 81.5% to 88.4%, reinforcing agent 10% to 15%, compatibilizer 1.5% to 2.0%, and opening agent 0.1% to 1.5%; The core layer includes the following raw material components by mass fraction: 63% to 68.5% of polylactic acid, 30% to 35% of reinforcing agent, and 1.5% to 2.0% of compatibilizer.
[0005] As a preferred technical solution of the present invention, the polylactic acid in the surface layer and the inner layer are respectively crystalline L-polylactic acid and non-crystalline racemic polylactic acid, wherein the weight ratio of crystalline polylactic acid: non-crystalline polylactic acid is 70:30; the polylactic acid in the core layer is crystalline L-polylactic acid.
[0006] As a preferred technical solution of the present invention, the reinforcing agent in the surface layer, inner layer and core layer is one or a combination of polyhydroxyalkanoate, polyglycolic acid (PGA), polyethylene 2,5-furandicarboxylate (PEF) or furan copolyester PECF.
[0007] As a preferred technical solution of the present invention, the furan copolyester PECF is a copolymer of 1,4-cyclohexanedimethanol (CHDM) and polyethylene furandicarboxylate (PEF), wherein the mass fraction of CHDM in the copolymer is 65-70%.
[0008] As a preferred technical solution of the present invention, the polyhydroxyalkanoate is one or a combination of poly 3-hydroxybutyrate (P3HB) and poly 3-hydroxyvalerate (P3HV).
[0009] As a preferred technical solution of the present invention, the compatibilizer is one or a combination of glycidyl methacrylate, diisocyanate, phosphite, maleic anhydride, and chitosan.
[0010] As a preferred technical solution of the present invention, the opening agent is one or a combination of silicon dioxide, talcum powder, and calcium carbonate.
[0011] As a preferred technical solution of the present invention, the thickness of the plastic base layer is 10μm to 50μm, wherein the thickness of the core layer is 8μm to 34μm, the thickness of the surface layer is 1μm to 8μm, and the thickness of the inner layer is 1μm to 8μm; the thickness of the aluminum oxide layer is 0.03μm to 0.06μm.
[0012] The preparation method of the high-barrier aluminum oxide-coated biaxially stretched polylactic acid film comprises the following steps: S1, putting the raw materials into three extruders according to the ratio of each layer, melting and plasticizing and mixing them evenly, respectively preparing the corresponding surface layer, core layer and inner layer, and then casting each layer through the T-type film head of the three-layer co-extrusion casting extruder head to obtain an unstretched film sheet; S2, placing the unstretched film sheet into a tentering machine for synchronous biaxial stretching or asynchronous biaxial stretching to obtain a biaxially stretched polylactic acid film; S3, placing the biaxially stretched polylactic acid film in a vacuum evaporation machine, evacuating the film, heating the aluminum wire and introducing oxygen to form an aluminum oxide layer on the inner surface of the film, thereby obtaining an aluminum oxide-coated biaxially stretched polylactic acid film. As a preferred technical solution of the present invention, the temperature of the extruder to the die head in step S1 is 220° C. to 250° C. The stretching ratio of the biaxially stretched polylactic acid film in step S2 is 2.0*2.0 to 4.0*4.0; and step S3 heats the aluminum wire and introduces oxygen.
[0013] The beneficial effects of the present invention are: 1. The high-barrier aluminum oxide-coated biaxially oriented polylactic acid film of the present invention is a degradable film, which has a positive significance for the treatment of plastic pollution; 2. The present invention adds P3HB and P3HV, PGA, PEF or PECF to the polylactic acid film. Due to the high crystallinity of P3HB, P3HV, PGA, PEF and PECF themselves and the heterogeneous nucleation effect on PLA, the crystallinity of the PLA blended film is improved, thereby improving the heat resistance of the film; at the same time, due to the addition of rigid particles, the rigidity and stiffness of the PLA blended film are improved, which is beneficial to the stability of the PLA film during vacuum evaporation treatment; 3. The present invention adds a large amount of compatibilizer during blending, which can effectively improve the compatibility of each component of the blend, and ensure that the P3HB, P3HV, PGA, PEF or PECF dispersed phase particles maintain a small particle size and do not agglomerate during blending. At the same time, adding a large amount of P3HB, P3HV or PGA under the premise of ensuring the particle size can form a percolation network in the PLA matrix, ensuring that the toughness of the blended film is not reduced or even improved while being enhanced, which is beneficial to the biaxial stretching process of the BOPLA film; and when the compatibilizer is chitosan, although it itself is a polysaccharide macromolecular structure with a high molecular weight, it has good solubility under acidic conditions, which can further promote the formation of the network structure without agglomeration.
[0014] 4. Compared with the aluminum-coated biaxially stretched polylactic acid film, the aluminum oxide-coated biaxially stretched polylactic acid film of the present invention has good transparency, and expands the application of high-barrier PLA film in the field of food packaging. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 Schematic diagram of the structure of biaxially oriented polylactic acid film coated with aluminum oxide.
[0015] In the figure: 1. Surface layer; 2. Core layer; 3. Inner layer; 4. Plastic base layer; 5. Metal-plated layer. DETAILED DESCRIPTION
[0016] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0017] Example 1 The present embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film, comprising a plastic base layer 4 and an aluminum oxide-coated layer 5, wherein the plastic base layer 4 is a biaxially oriented film, and its structure from top to bottom is a surface layer 1, a core layer 2 and an inner layer 3, and the inner layer 3 is combined with the metal-coated layer 5.
[0018] The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 57.1% crystalline L-polylactic acid and 24.4% non-crystalline racemic polylactic acid, 15% poly 3-hydroxybutyrate, 2.0% glycidyl methacrylate and 1.5% talcum powder; the core layer is composed of 68% crystalline L-polylactic acid, 30% poly 3-hydroxybutyrate and 2.0% glycidyl methacrylate.
[0019] The film thickness is as follows: the plastic base layer 4 has a thickness of 50 μm, the core layer 2 has a thickness of 40 μm, the surface layer 1 has a thickness of 5 μm, and the inner layer 3 has a thickness of 5 μm.
[0020] The metal-plated layer 5 is evacuated by a vacuum evaporator, and the aluminum wire is heated and oxygen is introduced to form an aluminum oxide layer on the surface of the film inner layer 3. The thickness of the aluminum oxide layer is 0.03 μm.
[0021] The method for preparing the high barrier aluminum oxide-coated biaxially stretched polylactic acid film of this embodiment comprises the following steps: 1. Put the raw materials into three extruders according to the ratio of the plastic base layer 4, melt and plasticize and mix evenly, respectively prepare the corresponding surface layer 1, core layer 2 and inner layer 3, and then cast each layer through the T-type film head of the three-layer co-extrusion casting extruder head to obtain an unstretched film sheet. The temperature from the extruder to the die head is 220°C.
[0022] 2. The unstretched film sheet is placed in a tentering machine for synchronous biaxial stretching to obtain a plastic base layer 4, with a stretching ratio of 3.0*3.0. 3. Place the biaxially oriented polylactic acid film in a vacuum evaporator, evacuate the film, heat the aluminum wire and introduce oxygen to form an aluminum oxide layer on the inner surface of the film to obtain an aluminum oxide-coated biaxially oriented polylactic acid film.
[0023] Example 2 This embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film.
[0024] The difference between this embodiment and embodiment 1 is: The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 57.1% crystalline L-polylactic acid and 24.4% non-crystalline racemic polylactic acid, 15% poly 3-hydroxyvalerate, 2.0% glycidyl methacrylate and 1.5% talcum powder; and the core layer is composed of 68% crystalline L-polylactic acid, 30% poly 3-hydroxyvalerate and 2% glycidyl methacrylate.
[0025] Example 3 This embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film.
[0026] The difference between this embodiment and embodiment 1 is: The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 57.1% crystalline L-polylactic acid and 24.4% non-crystalline racemic polylactic acid, 15% polyglycolic acid, 2.0% glycidyl methacrylate and 1.5% talcum powder; the core layer is composed of 68% crystalline L-polylactic acid, 30% polyglycolic acid and 2% glycidyl methacrylate.
[0027] Example 4 This embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film.
[0028] The difference between this embodiment and embodiment 1 is: The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 57.1% crystalline L-polylactic acid and 24.4% non-crystalline racemic polylactic acid, 15% polyethylene 2,5-furandicarboxylate, 2.0% glycidyl methacrylate and 1.5% talcum powder; the core layer is composed of 68% crystalline L-polylactic acid, 30% polyethylene 2,5-furandicarboxylate and 2% glycidyl methacrylate.
[0029] Example 5 This embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film.
[0030] The difference between this embodiment and embodiment 1 is: The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 57.1% crystalline L-polylactic acid and 24.4% non-crystalline racemic polylactic acid, 15% PECF, 2.0% glycidyl methacrylate and 1.5% talcum powder; the core layer is composed of 68% crystalline L-polylactic acid, 30% PECF and 2% glycidyl methacrylate.
[0031] PECF is a copolymer of 1,4-cyclohexanedimethanol (CHDM) and polyethylene furandicarboxylate (PEF), wherein the mass fraction of CHDM in the copolymer is 65%.
[0032] Example 6 This embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film.
[0033] The difference between this embodiment and embodiment 1 is: The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 57.1% crystalline L-polylactic acid and 24.4% non-crystalline racemic polylactic acid, 15% PECF, 1.5% maleic anhydride, 0.5 chitosan and 1.5% talcum powder; the core layer is composed of 68% crystalline L-polylactic acid, 30% polyglycolic acid, 1.5% maleic anhydride and 0.5% chitosan.
[0034] PECF is a copolymer of 1,4-cyclohexanedimethanol (CHDM) and polyethylene furandicarboxylate (PEF), wherein the mass fraction of CHDM in the copolymer is 65%.
[0035] Comparative Example 1 This comparative example provides a high-barrier aluminum-plated biaxially oriented polylactic acid film.
[0036] The difference between this comparative example and Example 1 is: The metal-plated layer 5 is evacuated by a vacuum evaporator, and the aluminum wire is heated to form an aluminum-plated layer on the surface of the film inner layer 3, and the thickness of the aluminum layer is 0.03 μm.
[0037] The difference between the preparation steps of this comparative example and Example 1 is: The biaxially oriented polylactic acid film is placed in a vacuum evaporation machine, vacuumized, and the aluminum wire is heated to form an aluminum layer on the inner surface of the film to obtain an aluminum-plated biaxially oriented polylactic acid film.
[0038] Comparative Example 2 This embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film.
[0039] The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 67.5% crystalline L-polylactic acid and 29.0% non-crystalline racemic polylactic acid, 2.0% glycidyl methacrylate and 1.5% talcum powder; the core layer is composed of 98.0% crystalline L-polylactic acid and 2.0% glycidyl methacrylate.
[0040] Comparative Example 3 This embodiment provides a high-barrier aluminum oxide-coated biaxially oriented polylactic acid film.
[0041] The formula of the plastic base layer 4 is as follows: the surface layer 1 and the inner layer 3 are composed of 57.1% crystalline L-polylactic acid and 24.4% non-crystalline racemic polylactic acid, 15% polyglycolic acid, 2.0% glycidyl methacrylate and 1.5% talcum powder; the core layer is composed of 69.7% crystalline L-polylactic acid, 30% polyglycolic acid and 0.3% glycidyl methacrylate.
[0042] In the step, since the film is relatively brittle and difficult to stretch, the unstretched film sheet is placed in a tentering machine for synchronous biaxial stretching to obtain the plastic base layer 4, and the stretching ratio is 1.5*1.5. Table 1 is a performance test table of the embodiments and comparative examples
[0043] The relevant tests in the table are carried out according to the following methods: 1. Elastic modulus, tensile strength and elongation at break Tested in accordance with GB / T1040.1-2018 Determination of tensile properties of plastics Part 1: General Principles and GBT1040.3-2006 Determination of tensile properties of plastics Part 3: Test conditions for films and sheets. 2. Water vapor transmission rate test Tested according to "GB1037-1988 Test method for water vapor permeability of plastic film and sheet - Cup method"; 3. Oxygen permeability test Tested according to GB / T1038-2000 Plastic Film and Sheet Gas Permeability Test Method-Pressure Difference Method; 4. Coating adhesion test The reference patent is CN100538323 "Method for testing the adhesion of the aluminum layer 20 of the vacuum aluminum-plated film using EAA film"; 5. Light transmittance test Tested according to GBT2410-2008 Determination of light transmittance and haze of transparent plastics.
[0044] The heat shrinkage test refers to the heat shrinkage test method in "GB / T 13519-2016 Polyethylene heat shrinkable film for packaging". As shown in Table 1, compared with Comparative Example 2, Examples 1-6 have higher elastic modulus and tensile strength at break, indicating that the addition of polyhydroxyalkanoate or polyglycolic acid increases the stiffness, rigidity and strength of the film. At the same time, Examples 1-6 have lower thermal shrinkage than Comparative Example 2, indicating that the addition of polyhydroxyalkanoate or polyglycolic acid improves heat resistance; the addition of PECF in Examples 5 and 6 makes the blend film have higher elongation at break and toughness than Examples 1-4, which can also make the film better biaxially stretched in the subsequent biaxial stretching step; Examples 1-6 have significantly improved light transmittance compared with Comparative Example 1, indicating that the aluminum oxide-coated biaxially stretched polylactic acid film has good transparency. At the same time, the low water vapor permeability and oxygen permeability of Examples 1-6 of the present invention indicate that the aluminum oxide-coated biaxially stretched polylactic acid film has good barrier properties. Compared with Example 3, Comparative Example 3 has a small amount of compatibilizer added, and a large amount of polyglycolic acid added in the polylactic acid matrix agglomerates to produce defects, and the film brittleness increases and it is difficult to stretch biaxially, so the film stretching ratio is relatively low, and the tensile elongation at break caused by biaxial stretching is less reduced, but at the same time, the rigidity, tensile strength at break, and transparency are lower than those of Example-1-6, and the water vapor permeability and oxygen permeability are increased, and the water and oxygen barrier properties of the film are reduced. The thermal shrinkage rate of the film in Example 6 is lower than that of other examples, indicating that 1.5% maleic anhydride and 0.5 chitosan can better reduce the thermal shrinkage rate.
[0045] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be thought of by a person skilled in the art within the technical scope disclosed by the present invention without creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.
Claims
1. A high barrier aluminum oxide coated biaxially oriented polylactic acid film, characterized in that: It includes a plastic base layer and an aluminum oxide layer, wherein the film base layer is a three-layer co-extruded biaxially stretched film consisting of a surface layer, a core layer and an inner layer in sequence; the inner layer is combined with the aluminum oxide layer; The surface layer and the inner layer include the following raw material components by mass fraction: polylactic acid 81.5% to 88.4%, reinforcing agent 10% to 15%, compatibilizer 1.5% to 2.0%, and opening agent 0.1% to 1.5%; The core layer includes the following raw material components by mass fraction: 63% to 68.5% of polylactic acid, 30% to 35% of reinforcing agent, and 1.5% to 2.0% of compatibilizer.
2. The high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 1, characterized in that: The polylactic acid in the surface layer and the inner layer is respectively crystalline L-polylactic acid and non-crystalline racemic polylactic acid, wherein the weight ratio of crystalline polylactic acid to non-crystalline polylactic acid is 70:30; the polylactic acid in the core layer is crystalline L-polylactic acid.
3. The high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 1, characterized in that: The reinforcing agent added to the surface layer, the inner layer and the core layer is one or a combination of polyhydroxyalkanoate, polyglycolic acid, polyethylene 2,5-furandicarboxylate or furan copolyester.
4. The high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 3, characterized in that: The polyhydroxyalkanoate is one or a combination of poly 3-hydroxybutyrate and poly 3-hydroxyvalerate.
5. The high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 3, characterized in that: The furan copolyester PECF is a copolymer of 1,4-cyclohexanedimethanol (CHDM) and polyethylene furandicarboxylate (PEF), wherein the mass fraction of CHDM in the copolymer is 65-70%.
6. The high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 1, characterized in that: The compatibilizer is one or a combination of glycidyl methacrylate, diisocyanate, phosphite, maleic anhydride and chitosan.
7. The high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 1, characterized in that: The opening agent is one or a combination of silicon dioxide, talcum powder and calcium carbonate.
8. The high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 1, characterized in that: The thickness of the plastic base layer is 10 μm to 50 μm, wherein the thickness of the core layer is 8 μm to 34 μm, the thickness of the surface layer is 1 μm to 8 μm, and the thickness of the inner layer is 1 μm to 8 μm; the thickness of the aluminum oxide layer is 0.03 μm to 0.06 μm.
9. The method for preparing the high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1, putting the raw materials into three extruders according to the ratio of each layer, melting and plasticizing and mixing them evenly, respectively preparing the corresponding surface layer, core layer and inner layer, and then casting each layer through the T-type film head of the three-layer co-extrusion casting extruder head to obtain an unstretched film sheet; S2, placing the unstretched film sheet into a tentering machine for synchronous biaxial stretching or asynchronous biaxial stretching to obtain a biaxially stretched polylactic acid film; S3, placing the biaxially stretched polylactic acid film in a vacuum evaporation machine, evacuating the film, heating the aluminum wire and introducing oxygen to form an aluminum oxide layer on the inner surface of the film, thereby obtaining an aluminum oxide-coated biaxially stretched polylactic acid film.
10. The method for preparing the high barrier aluminum oxide-coated biaxially oriented polylactic acid film according to claim 9, characterized in that: In step S1, the temperature of the extruder to the die head is 220° C. to 250° C.; in step S2, the stretching ratio of the biaxially stretched polylactic acid film is 2.0*2.0 to 4.0*4.0; and in step S3, the aluminum wire is heated and oxygen is introduced.
Citation Information
Patent Citations
Biaxially oriented polylactic acid functional film and preparation method thereof
CN117507538A
Linear easy-to-tear polylactic acid film and preparation method thereof
CN118342873A
Ultrahigh-barrier heat-sealable biaxially oriented film and preparation method thereof
CN118952806A
Cited By
Degradable heat-sealing type two-way stretching polylactic acid high-barrier packaging film and preparation method thereof
CN120396461A